Immune modulating effects of NKT cells in a physiologically low dose Leishmania major infection model after αGalCer analog PBS57 stimulation. - Klaus G Griewank; Beate Lorenz; Michael R Fischer; Louis Boon; Susanna Lopez Kostka; Esther von Stebut (Public Library of Science (PLoS), 2014)
Leishmaniasis is a parasitic infection affecting ∼12 million people worldwide, mostly in developing countries. Treatment options are limited and no effective vaccines exist to date. Natural Killer T (NKT) cells are a conserved innate-like lymphocyte population with immunomodulating effects in various settings. A number of reports state a role of NKT cells in different models of Leishmania infection. Here, we investigated the effect of NKT cells in a physiologically relevant, intradermal low dose infection model. After inoculation of 103 infectious-stage L. major, comparable numbers of skin-immigrating NKT cells in both susceptible BALB/c mice and resistant C57BL/6 mice were noted. Compared to their wild type counterparts, NKT cell-deficient mice on a C57BL/6 background were better able to contain infection with L. major and showed decreased IL-4 production in cytokine analysis performed 5 and 8 weeks after infection. Low doses of the NKT cell stimulating αGalCer analog PBS57 applied at the time of infection led to disease exacerbation in C57BL/6 wild-type, but not NKT-deficient mice. The effect was dependent both on the timing and amount of PBS57 administered. The effect of NKT cell stimulation by PBS57 proved to be IL-4 dependent, as it was neutralized in IL-4-deficient C57BL/6 or anti-IL-4 antibody-treated wild-type mice. In contrast to C57BL/6 mice, administration of PBS57 in susceptible BALB/c mice resulted in an improved course of disease. Our results reveal a strain- and cytokine-dependent regulatory role of NKT cells in the development of immunity to low dose L. major infections. These effects, probably masked in previous studies using higher parasite inocula, should be considered in future therapy and immunization approaches.